Management of Acute Myocardial Infarction in Patients With Dementia: Data From SveDem, the Swedish Dementia Registry - Cermakova, Pavla; Szummer, Karolina; Johnell, Kristina; Fastbom, Johan; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (Journal of the American Medical Directors Association, 2017)
OBJECTIVES: We aimed to (1) study factors that determine the use of invasive procedures in the management of acute myocardial infarction (AMI) in patients with dementia and (2) determine whether the use of invasive procedures was associated with their better survival. DESIGN: Cohort study based on patients registered in the Swedish Dementia Registry (SveDem), 2007-2012. Median follow-up time was 228 days. SETTING: Patients diagnosed with dementia in specialist memory clinics and primary care units in Sweden. PARTICIPANTS: A total of 525 patients with dementia who suffered AMI (mean age 89 years, 54% women). MEASUREMENTS: Information on AMI and use of invasive procedures (coronary angiography and percutaneous coronary intervention) was obtained from Swedish national health registers. Binary logistic regression was applied to study associations of patients' characteristics with the use of invasive procedures; odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Survival was analyzed with Kaplan-Meier curves; log-rank test was used to compare survival of patients who received an invasive procedure versus those who did not receive it. Cox regression was applied to study association of the invasive procedures with all-cause mortality; hazard ratios (HRs) with 95% CIs were calculated. RESULTS: One hundred ten patients (21%) with dementia received an invasive procedure in the management of AMI. After multivariate adjustment, lower age and higher global cognitive status were associated with the use of invasive procedures. The invasively managed patients survived longer (P = .001). The use of invasive procedures was associated with a lower risk of all-cause mortality, adjusting for type of AMI and dementia disorder, age, gender, registration unit, history of AMI and comorbidity score (HR 0.35, 95% CI 0.21-0.59), or total number of drugs (HR 0.34, 95% CI 0.20-0.58). CONCLUSION: Age and cognitive status determine the use of invasive procedures in patients with dementia. This study suggests that the invasive management of AMI has a benefit for survival of patients with dementia.
Keywords: Registries; Švédsko; dementia; coronary angiography; Humans; demence; analýza přežití; registrace; Sweden; kohortové studie; Female; Aged; senioři; lidé; infarkt myokardu; Survival Analysis; survival; Cohort Studies; ženské pohlaví; Male; Acute myocardial infarction; Retrospective Studies; Myocardial Infarction; Aged, 80 and over; Dementia; senioři nad 80 let; retrospektivní studie; percutaneous coronary intervention; mužské pohlaví